Features of calcium hexaaluminate formation in alumina-zirconia ceramics - Nina Cherkasova; Kristina Antropova; Ruslan Kuzmin; Kemal Emurlaev; Ivanna Kuchumova; Nomina Burkhinova; Yulia Zobova (Chimica Techno Acta)
Alumina-zirconia composites containing calcium hexaaluminate in the amount from 0 to 15 wt.% were investigated. The materials were obtained by water dispersion, granulation, axial pressing, and free sintering. Density and open porosity were determined by the hydrostatic weighing method. Phase analysis was performed using synchrotron radiation. Structural investigations were conducted using scanning and transmission electron microscopy. Vickers hardness was determined at a load of 10 kg. Fracture toughness was determined by the indentation method. With increasing CaAl12O19 content in the composites, the relative density decreased from 98.5% to 91.8%, and the open porosity increased from 0.2 to 1.4%. The lattice parameters of t-ZrO2 crystal lattice did not change up to 12 wt.% CaAl12O19, and the degree of tetragonality was 1.435. The degree of tetragonality decreased for the material with 15 wt.% CaAl12O19 and reached 1.420. The lattice parameters of CaAl12O19 decreased with increasing content. Platelet size increased with increasing calcium hexaaluminate content. For the materials containing up to 9 wt.% CaAl12O19, the average length of the platelets was 2 μm, the width was 0.4 μm, and the aspect ratio was 5. For the material with maximum calcium hexaaluminate content, the average length of the platelets was 4.2 μm, the width was 0.6 μm, and the aspect ratio was 7. With increasing CaAl12O19 content, the hardness decreased from 1700±25 to 1390±30 Hv, and the critical stress intensity factor increased by 34% to 6.7±0.3 MPa·m1/2.